Endoscopic diagnosis of acute intestinal GVHD following allogeneic hematopoietic SCT: A retrospective analysis in 175 patients - Kreisel, Wolfgang; Potthoff, Karin (Bone marrow transplantation, 2011)
Diagnosis of acute intestinal GVHD (aGVHD) following allogeneic hematopoietic cell transplantation is based on clinical symptoms and histological lesions. This retrospective analysis aimed to validate the 'Freiburg Criteria' for the endoscopic grading of intestinal aGVHD. Grade 1: no clear-cut criteria; grade 2: spotted erythema; grade 3: aphthous lesions; and grade 4: confluent defects, ulcers, denudation of the mucosa. Having excluded patients with infectious diarrhea, we evaluated 175 consecutive patients between January 2001 and June 2009. Setting a cutoff between grade 1 (no change in therapy) and grade 2 (intensification of immunosuppression), macroscopy had a sensitivity of 89.2% (95% confidence interval (CI): 80.4-94.9%), a specificity of 79.4% (95% CI: 69.6-87.1%), a positive-predictive value of 79.6% (95% CI: 70.0-87.2%) and a negative-predictive value of 89.0% (95% CI: 80.2-94.9%). In all, 20% of patients with aGVHD in the lower gastrointestinal tract (GIT) had lesions only in the terminal ileum. In all patients with aGVHD ≥2 of the upper GIT, typical lesions were also found in the lower GIT. Ileo-colonoscopy showed the highest diagnostic yield for aGVHD. In conclusion, the 'Freiburg Criteria' for macroscopic diagnosis of intestinal aGVHD provide high accuracy for identifying aGVHD ≥2.